Linguistic security of Arabic in the context of globalization - Abdussalam, Ahmad Shehu (IIUM Press, 2009)
In the context of globalization, security is required for the survival of a language and its native culture, just as language itself has become an important means of providing security for its native and non-native speakers, and Arabic is a living case. Security for Arabic is essential due to the great impact of globalization which is a source of concern for the Arabs, and security with Arabic is as equally essential for non-Arabs in their interaction with the Arab government, people and culture, as it is vital for the security of the Arabs themselves. This paper investigates the modes of relationship between language and security, and analyzes points of concern in the context of globalization for providing security "for Arabic" and "with Arabic".